Gastric Xylobezoar Treated with Continuous Enteral Coca-Cola® Infusion - Gopinathan Gangadharan Nambiar; Eyad Hanna; Julia Shelton; Rose Lee (Case Reports in Pediatrics)
Xylobezoar is a rare clinical condition in which undigested paper becomes trapped in the gastrointestinal tract causing varying degrees of gastrointestinal obstruction. This condition can be suspected in children with a history of gastric surgeries, decreased gastrointestinal motility, or pica. Xylobezoar presents with symptoms ranging from chronic abdominal pain to gastrointestinal perforation. Surgical intervention is often required as endoscopic removal is challenging and not always successful. Chemical dissolution has been shown to be effective in treating certain bezoars. Here, we report a case of a pediatric patient with xylobezoar who was successfully treated with continuous enteral Coca-Cola® infusion.